Clinical Practice Guidelines: Management of Ischaemic Stroke (3rd edition) - Society of Neurosciences, Malaysian (Journal Of Cardiovascular, Neurovascular & Stroke, 2021)
The 1st Clinical Practice Guideline (CPG) on the management of ischaemic stroke was published in 2006 and the second edition was published in 2012. Since then, there was a rapid development in the management of acute stroke, mainly with the improvement and advancement of reperfusion therapy, encompassing both medical thrombolysis and mechanical thrombectomy. Furthermore, the importance of timely intervention, especially in the emergency department, had significantly improved the outcome in stroke patients. Therefore, this current CPG emphasizes the hyperacute management and has introduced new chapters, for example, emergency medical services. With the growing numbers of elderly population in Malaysia, we have also included a new chapter on stroke in the older person. This 3rd edition was developed to provide a clear and concise approach based on current evidence with the focus being on the efforts to reduce time and improve pre-hospital care. We have summarised and adapted relevant clinical trials data and published literatures to our local practice.